2021
DOI: 10.3390/nu14010137
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols—Gut Microbiota Interrelationship: A Transition to a New Generation of Prebiotics

Abstract: The present review summarizes the studies carried out on this topic in the last five years. According to the new definitions, among all the compounds included in the group of prebiotics, polyphenols are probably the most important secondary metabolites produced by the plant kingdom. Many of these types of polyphenols have low bioavailability, therefore reaching the colon in unaltered form. Once in the colon, these compounds interact with the intestinal microbes bidirectionally by modulating them and, consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(128 citation statements)
references
References 170 publications
(192 reference statements)
5
123
0
Order By: Relevance
“…However, more than 83% would recommend prebiotics if proven by literature [70]. Confusion about the differences between probiotics and prebiotics was also common between healthcare providers in another study [80]. The scarce data from the scientific community on prebiotics could be responsible for the lack of knowledge of healthcare providers and highlights the importance of education in order to provide recommendations to patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, more than 83% would recommend prebiotics if proven by literature [70]. Confusion about the differences between probiotics and prebiotics was also common between healthcare providers in another study [80]. The scarce data from the scientific community on prebiotics could be responsible for the lack of knowledge of healthcare providers and highlights the importance of education in order to provide recommendations to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known probiotic strains of Lactobacilli and Bifidobacteria are directly involved in the gut and mental homeostasis, especially because of their external structure that does not comprise pro-inflammatory LPS chains like the pathogenic strains of Salmonella or Escherichiacoli ( 243 ). Lactobacilli and Bifidobacteria are categorized as psychobiotics for their psychotropic properties in terms of behavior improvement in depressed and anxious individuals ( 243 , 254 , 255 ). In a study conducted by Liu et al ( 254 ) on adult mice with and without induced stress in early life, it was observed that Lactobacillus plantarum strain PS128 reduces depression and anxiety-like behavior in tested animals.…”
Section: Probiotic Formulations As a Potential Therapy For Neurologic...mentioning
confidence: 99%
“…Prebiotics and probiotics administered as food supplements maintain the host’s general health status because of their resistance through the gastrointestinal tract, their good adhesivity to the intestinal mucosa, and their specific metabolites delivered in systemic circulation ( 264 266 ). Prebiotics, in particular, are non-viable food components that act indirectly by selectively stimulating the growth and activities of beneficial microorganisms in the gastrointestinal system, resulting in beneficial effects on the host, such as gastrointestinal, central nervous, immune, and cardiovascular system protection ( 255 , 267 ). Few clinical research studies have investigated the neuropsychiatric effects of prebiotic formulations.…”
Section: Probiotic Formulations As a Potential Therapy For Neurologic...mentioning
confidence: 99%
“…These studies differ in terms of the type of animals or subject population, disease state, duration and dose and type of bioactive compounds. A recent review of Plamada and Vodnar [ 142 ] presents polyphenol-gut microbiota interactions. The effect of polyphenols on the gut barrier functions was summarized in an excellent review [ 140 ]; therefore, in this review, only a brief summary will be presented.…”
Section: Prebioticsmentioning
confidence: 99%